The Limits of Defining Identity in Religion-Gender Conflicts: A Response to Patrick Parkinson. Issue 1 (26th January 2023) - Portuondo, Laura; Haupt, Claudia E.
Abstract: In his article "Gender Identity Discrimination and Freedom of Religion, " Patrick Parkinson raises the important question of how the government should reconcile conflicts between the rights of religious people and the rights of transgender and gender-nonconforming people. By focusing on whether gender identity is best defined as a medical issue or a belief system, however, Parkinson does little to answer it. Whether gender identity is a medical issue may be relevant to determining the sincerity of an individual's faith-based objection to complying with an antidiscrimination law. It has no bearing, however, on the strength of trans and gender-nonconforming individuals' countervailing interest in being protected from discrimination. Defining gender identity as a belief system does no more to undermine this interest. This should be apparent to defenders of religious exemptions, who assert that belief systems offer a basis for extending, rather than contracting, legal protections. Characterizing an individual's gender identity as either a medical issue or a belief system thus does not show why that individual's interests should give way to the interests of religious objectors through an exemption. To reach this conclusion, one must instead turn to other values, such as those implicit—though inadequately defended—in Parkinson's article.